ANALISIS TRANSMISI KEBIJAKAN MONETER MELALUI INSTRUMEN KONVENSIONAL DAN SYARIAH TERHADAP INFLASI DI INDONESIA PERIODE 2014.6-2019.12 - Zainul Hadi; Mansur Afifi; Taufiq Chaidir (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
This study aims to analyze the response and time leg of monetary policy through conventional and sharia instruments to inflation in Indonesia. This type of research is explanatory to test hypotheses that state a causal relationship between two or more variables with little bias and increase trust. The analytical tool used is VAR / VECM. the variable used in research is INFLATION, RSBI, RPUAB, CREDIT, GWMK, SBIS, PUAS, FINANCING and GWMS. based on the results of the Impulse Response Function (IRF) that RSBI, RPUAB, CREDIT, GWMK, SBIS and PUAS responded positively to inflation even though at the beginning of the period it was still unstable and from the sixth to the tenth period had reached balance. While the two financing instruments FINANCING and GWMK respond negatively to inflation. Then the results of the analysis of variance decomposition of the model, both RSBI, RPUAB, CREDIT, GWMK, SBIS, PUAS, FINANCING and GWMK have a small average contribution. Inflation itself has a greater contribution and the time period required by the transmission of monetary policy through conventional and sharia instruments to achieve the ultimate goal of inflation for three months.